Parasite-Probiotic Interactions in the Gut: Bacillus sp. and Enterococcus faecium Regulate Type-2 Inflammatory Responses and Modify the Gut Microbiota of Pigs During Helminth Infection - Myhill, Laura J.; Stolzenbach, Sophie; Mejer, Helena; Krych, Lukasz; Jakobsen, Simon R.; Kot, Witold; Skovgaard, Kerstin; Canibe, Nuria; Nejsum, Peter; Nielsen, Dennis S.; Thamsborg, Stig M.; Williams, Andrew R. (Frontiers in Immunology, 2022)
Dietary probiotics may enhance gut health by directly competing with pathogenic agents and through immunostimulatory effects. These properties are recognized in the context of bacterial and viral pathogens, but less is known about interactions with eukaryotic pathogens such as parasitic worms (helminths). In this study we investigated whether two probiotic mixtures (comprised of Bacillus amyloliquefaciens, B. subtilis, and Enterococcus faecium [BBE], or Lactobacillus rhamnosus LGG and Bifidobacterium animalis subspecies Lactis Bb12 [LB]) could modulate helminth infection kinetics as well as the gut microbiome and intestinal immune responses in pigs infected with the nodular worm Oesophagostomum dentatum. We observed that neither probiotic mixture influenced helminth infection levels. BBE, and to a lesser extent LB, changed the alpha- and beta-diversity indices of the colon and faecal microbiota, notably including an enrichment of faecal Bifidobacterium spp. by BBE. However, these effects were muted by concurrent O. dentatum infection. BBE (but not LB) significantly attenuated the O. dentatum-induced upregulation of genes involved in type-2 inflammation and restored normal lymphocyte ratios in the ileo-caecal lymph nodes that were altered by infection. Moreover, inflammatory cytokine release from blood mononuclear cells and intestinal lymphocytes was diminished by BBE. Collectively, our data suggest that selected probiotic mixtures can play a role in maintaining immune homeostasis during type 2-biased inflammation. In addition, potentially beneficial changes in the microbiome induced by dietary probiotics may be counteracted by helminths, highlighting the complex inter-relationships that potentially exist between probiotic bacteria and intestinal parasites.